Is Microfracture Necessary? Acetabular Chondrolabral Debridement/Abrasion Demonstrates Similar Outcomes and Survival to Microfracture in Hip Arthroscopy: A Multicenter Analysis - Hevesi, Mario; Bernard, Christopher; Hartigan, David E; Levy, Bruce A; Domb, Benjamin G; Krych, Aaron J (The American journal of sports medicine, 2019)
Hip arthroscopy is becoming more advanced and commonly performed. However, significant controversy exists regarding whether high-grade acetabular cartilage lesions should be treated with debridement/abrasion or microfracture. In addition, patients treated with microfracture are subject to extended protected weightbearing rehabilitation to mitigate risk of subchondral plate fracture and to protect fibrocartilage tissue formation. To determine the midterm patient-reported outcomes and failure rate of patients with grade 3 and 4 acetabular labrum articular disruption (ALAD) lesions managed with debridement/abrasion or microfracture. Cohort study; Level of evidence, 3. Primary arthroscopic labral repair cases at 2 centers from November 2008 to April 2016 were reviewed for patients aged <55 years with unipolar ALAD grade 3 and 4 chondrolabral acetabular delamination. Patients undergoing microfracture and debridement/abrasion were compared using the visual analog pain scale (VAS), modified Harris Hip Score (mHHS), and Hip Outcome Score-Sports-Specific Subscale (HOS-SSS) to determine predictors of outcomes and failure. A total of 113 hips in 110 patients (66 males, 44 females; mean age, 34.5 ± 1.1 years) undergoing debridement/abrasion (n = 82) or microfracture (n = 31) were followed for a mean of 4.9 years (range, 2.0-8.5 years). Lesion size was not statistically different between the debridement/abrasion (1.3 ± 1.0 cm ) and microfracture cohorts (1.4 ± 1.0 cm ) ( P = .47). Patients undergoing debridement/abrasion achieved 3.6-point mean improvements in VAS ( P < .01), 21.2-point improvements in mHHS ( P < .01), and 25.4-point improvements in HOS-SSS ( P < .01), which were not significantly different from those observed in microfracture patients ( P≥ .20). The 5-year rate of survival free of revision surgery was 84.0% in the debridement/abrasion group and 85.6% in the microfracture group ( P = .78). The cartilage treatment technique was found not to be predictive of revision risk during both univariate (hazard ratio [HR], 1.01; P = .98) and multivariate (HR, 0.93; P = .90) analysis accounting for patient age, lesion grade, and acetabular coverage. Patients undergoing debridement/abrasion of high-grade unipolar acetabular cartilage lesions demonstrate similar outcome scores and revision rates compared with those of patients undergoing microfracture. These outcomes support the consideration of preferential debridement/abrasion at the discretion of the treating surgeon to optimize recovery while maintaining established positive outcomes after hip arthroscopy.